Transcriptional profiling of extraintestinal Escherichia coli exposed to cranberry pomace extracts alone or in combination with ceftriaxone - Quail Das; Teri-Lyn Hasted; Teri-Lyn Hasted; Dion Lepp; Xianhua Yin; Joshua Tang; Gabhan Chalmers; Kelly Ross; Patrick Boerlin; Moussa S. Diarra (Frontiers in Sustainable Food Systems, 2023)
Extraintestinal pathogenic Escherichia coli (ExPEC) includes several serotypes that have been associated with colibacillosis in poultry, as well as urinary tract infections and newborn meningitis in humans. This study investigated the antimicrobial activities of ceftriaxone (AXO) and cranberry pomace extracts (CRAN) alone or in combination (CC) against multidrug-resistant (MDR) ExPEC from broiler. The growth-inhibitory activity of CRAN and synergy tests by a checkerboard method were determined in cation-adjusted Mueller–Hinton broth (CAMHB). The transcriptomic profile of the MDR E. coli O7:H18 (ST38) grown in CAMHB supplemented with sub-inhibitory concertation of CRAN and AXO alone or in combination was obtained by RNA-seq. The MIC of CRAN for all isolates was 16 mg/mL. An additive activity was observed between 4 mg/mL of CRAN and 4 μg/mL of AXO. Compared to the control, the transcriptomic analysis revealed that 4 mg/ml of (1/4MIC) CRAN and its combination with 4 μg/mL of (1/8MIC) AXO (CC) exposures resulted in 727 and 712 differentially expressed genes, respectively (false discovery rate < 0.001 and log2-fold change > 2), in the studied E. coli. Major virulence genes including adhesins (fim, flg, csg, and yad), protectins (omp, tra, waa, and hly), secretion systems (hof, pho, and vir), and quorum sensing (lsr), which are energetically expensive for bacteria, were downregulated. Most importantly, 1/4MIC of CRAN or CC downregulated the β-lactamase blaCMY-2 and efflux pump including tolC, mdtEIJ, gadEW, and their regulator gene evgS, while upregulating the cysteine biosynthesis and oxidative stress-related regulatory genes including cys, dmlA, sbp, nrdGHI, soxSR, and rpoH. Downregulation of multiple enzymes involved in TCA cycles and upregulation of Fe–S cluster coordinated by Cys and Isc proteins reflect the regulation of energy metabolism of the studied E. coli upon CRAN or CC exposure. The downregulation of outer membrane protein genes that control permeability barriers, along with different antimicrobial resistance genes, demonstrates that CRAN may have the unique potential to enhance the antimicrobial activities of third-generation cephalosporins such as AXO against MDR E. coli.